Gastroschisis in newborns at Hospital Nacional Daniel A. Carrión. Case series in 5 years - Lacunza Paredes, Rommel Omar (2017)
Gastroschisis is a congenital defect of the abdominal wall that allows externalization of the abdominal contents; prognosis depends on the associated intestinal complications. Prenatal detection of cases with risk of complex gastroschisis is important. Objective: To describe the epidemiological characteristics of newborns with gastroschisis occurring at a national hospital. Design: Case series. Institution: Hospital Nacional Daniel A. Carrion (HNDAC), Lima, Peru. Patients: Newborns with gastroschisis. Methodology: All live newborns with the diagnosis of gastroschisis in a period of 5 years were studied. Cases born in other institutions or with insufficient data were excluded. Main outcome measures: Characteristics of newborns with gastroschisis and their management. Results: 17 cases were reported with an incidence of 9.7/1 000 live newborns and with a perinatal mortality of 14%; 64.3% were born to an adolescent mother, of which 78% carried their first pregnancy. The main delivery mode was cesarean section (71.4%). There were poor records of ultrasonographic predictors of intestinal complications. Primary closure was performed in 28.6% of cases. The first case of death occurred after surgery with silo and died from sepsis. The second case had intestinal atresia requiring multiple surgeries and died due to massive atelectasis. Conclusions: It is necessary to standardize the assessment and registration of various prognostic markers in fetal gastroschisis. More and better documented series are necessary.